Analysis of intact prophages in genomes of Paenibacillus larvae: An important pathogen for bees - Ribeiro, Henrique G.; Nilsson, Anna; Melo, Luís D. R.; Oliveira, Ana (Frontiers in Microbiology, 2022)
Paenibacillus larvae is the etiological agent of American Foulbrood (AFB), a highly contagious and worldwide spread bacterial disease that affects honeybee brood. In this study, all complete P. larvae genomes available on the NCBI database were analyzed in order to detect presence of prophages using the PHASTER software. A total of 55 intact prophages were identified in 11 P. larvae genomes (5.0 ± 2.3 per genome) and were further investigated for the presence of genes encoding relevant traits related to P. larvae. A closer look at the prophage genomes revealed the presence of several putative genes such as metabolic and antimicrobial resistance genes, toxins or bacteriocins, potentially influencing host performance. Some of the coding DNA sequences (CDS) were present in all ERIC-genotypes, while others were only found in a specific genotype. While CDS encoding toxins and antitoxins such as HicB and MazE were found in prophages of all bacterial genotypes, others, from the same category, were provided by prophages particularly to ERIC I (enhancin-like toxin), ERIC II (antitoxin SocA) and ERIC V strains (subunit of Panton-Valentine leukocidin system (PVL) LukF-PV). This is the first in-depth analysis of P. larvae prophages. It provides better knowledge on their impact in the evolution of virulence and fitness of P. larvae, by discovering new features assigned by the viruses.